'An Art That Reaches beyond the World': Sir Arthur Bliss and Music as Spirituality - McCullough, Matthew (Religions, 2022)
Throughout his life, British composer Sir Arthur Bliss (1891–1975) placed great importance on the value of music. He saw it as something that could bring peace and healing and as an ‘art that reaches beyond the world.’ In his artistic creed, set out in 1934, Bliss speaks of music as inherently linked with emotion in its form as a crucial mode of human expression, both in listening and in its composition. His philosophies on these are fairly well documented; he spoke publicly on contemporary composition and wrote extensively on his own experiences with music, not least in his autobiography, As I Remember. Equally, he and his wife both write of his music as an embodiment of the ‘private’ Arthur Bliss, one in which we might find something of the man hidden from the general public. With this in mind, and given Bliss’s view of music as something with spiritual value, this article aims to examine his previously neglected philosophies on composition, exploring themes of emotion, identity, and destiny through an exegesis of his writings, lectures, and broadcasts, and by probing the composition and context of A Colour Symphony, Meditations on a Theme by John Blow, and Shield of Faith. Using a lens of Douglas Davies’ idea-value-belief series supported by Davies’ theory of cultural intensification it argues that, for Bliss, music can be seen as more than an idea—it was a value, a belief, and perhaps even a religious belief. In its conclusion, this article suggests that we can uncover a form of spirituality in Bliss’s attitude to music and view this attitude as something which acts ‘against death’.